KETAKUTAN YANG BERALASAN PADA PENGUNGSI PENYANDANG DISABILITAS (Well-Founded Fear within Refugees with Disabilities) - Maya Indrasti Notoprayitno (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2021)
Persons with disabilities are vulnerable group and would be found anywhere in any situation. They become refugees since their conditions of persecution and they should leave out from their country. Unfortunately, the problem occured when persons with mental disabilities  could not indicate their well-founded fear as stated in the 1951 Convention on the Status of Refugees. Regarding the problem, Convention on the Rights of Persons with Disabilities (CRPD) may be the answer to settle the problem since CRPD is the human rights approach to disability and recognizes the right of persons with disabilities to equality in most aspects of life. From CRPD, refugees with disabilities can show a well-founded fear thus giving a hope for them in obtaining refugee status and gaining access equivalent to refugees in general. UNHCR uses the CRPD as a reference in carrying out the responsibilities and commitments for the rights of refugees with disabilities.